Some Problems of Housing Development in Yugoslavia - Čaldarović, Ognjen (Array, 1987)
Major developmental problems of housing in the former Yugoslavia are discussed in the paper. It is stressed that less multi-storey and dense housing structures should be build more. Housing rights and priovatization of housing as well as social housing are also discussed.